2008
DOI: 10.1038/eye.2008.318
|View full text |Cite
|
Sign up to set email alerts
|

The association between multifocal electroretinograms and OCT retinal thickness in retinitis pigmentosa patients with good visual acuity

Abstract: Aims To investigate relationships between retinal morphology and retinal function in patients with retinitis pigmentosa (RP) using optical coherence tomography (OCT) and multifocal electroretinography (mfERG). Methods In all, 14 patients with RP who had visual acuities of 0.2 logMAR or better and Humphrey central fields of 101 or larger participated in the study along with 16 normal control subjects. The amplitudes and timings of the mfERG responses were compared with spatially corresponding measures of retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
3
10
0
1
Order By: Relevance
“…Sugita et al in a focal macular ERG study stated that preserved macular morphology does not necessarily guarantee reserved electrical potential in RP patients 12. In a multifocal ERG study, Wolsley et al reported that preserved timing in the central retina, despite significant disruption of the retinal laminar structure, could be suggestive of inner retinal remodeling or functional redundancy 13. They also stated that cone-system activity shown in multifocal ERG responses could be related to the thickness of the photoreceptor layer in the macular region.…”
Section: Discussionmentioning
confidence: 99%
“…Sugita et al in a focal macular ERG study stated that preserved macular morphology does not necessarily guarantee reserved electrical potential in RP patients 12. In a multifocal ERG study, Wolsley et al reported that preserved timing in the central retina, despite significant disruption of the retinal laminar structure, could be suggestive of inner retinal remodeling or functional redundancy 13. They also stated that cone-system activity shown in multifocal ERG responses could be related to the thickness of the photoreceptor layer in the macular region.…”
Section: Discussionmentioning
confidence: 99%
“…While the mfERG amplitude was preserved within the area of 0-6°, the photoreceptor segments were relatively intact [33]. The patients with longer EZ lines had significantly larger mfERG amplitudes than the patients with shorter or absent EZ lines [27].…”
Section: Photoreceptor Segmentsmentioning
confidence: 99%
“…It helps in examining local functional losses in various retinal diseases such as glaucoma, diabetic retinopathy, agerelated macular degeneration and retinitis pigmentosa [1][2][3][4][5][6][7][8][9][10][11]. The conventional mfERG signals were reported to mainly originate from bipolar cells [12,13].…”
Section: Introductionmentioning
confidence: 99%